Método clínico fonoaudiológico: quando o discurso toma a palavra - Kokanj, Andréa Siqueira (2003)
The objective of this article is to discuss the clinical method in the field of Speech and Language Therapy. In this perspective, initialy, is shown the current condition of the art in the field of Language Therapy, discussing the reductionism to which the clinical method is submited, given the fundamental mistakes made between "method" and "technic" derived frem the Medical Clinic and applied to the field of Language Therapy. Is also stated, in this study, the main principies that guide the refered Language Therapy clinical method, supported, in one side, on Psychoanalisys on. its considerations on clinic and, in the other side, on Linguistics and its considerations over language. Understanding the clinical method as a clinical structure in action, in function, I bring on discussion an attempt to formalize it, submiting to an discoursive perspective, on which the pathologic language of the subject is involved